POLA PEMBERIAN MP-ASI DAN STATUS GIZI BAYI USIA 6-12 BULAN DI WILAYAH KERJA UPT KESMAS TAMPAKSIRING I - Putu Aurilia Chlaresta Putri; I G A Ari Widarti; Ni Made Dewantari (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2018)
Food companion ASI (MP-ASI) is food or beverages that contain nutrients that are given to infants or children aged 6-24 months to meet the needs of its nutrition value. The purpose of this research is to know the pattern of the giving of the MP-ASI and nutritional status of infants. The study was observational research with Cross Sectional design. Research done in the area of UPT Kesmas Tampaksiring I on May 2018. The unit of analysis in the study is baby age 6-12 months totaled 55 samples. Identity data and pattern of granting MP ASI gathered through interviews using questionnaire and conducted weighing weight samples. The way of processing data type MP-ASI with categorizing into MP-ASI purchased (manufacturer) and MP-ASI homemade (local). Data processing age awarding MP-ASI will be categorized into less suitable ( 6 months) and appropriate (? 6 months) grant of frequency Data MP-ASI mingled with categorizing into appropriate and inappropriate. To find out the nutritional status is done by calculating the value of the z-score (W/U) and then categorized into malnutrition, nutrition, nutrition good nutrition and more. The data presented in the form of a table of frequency distribution and cross-tabulated, analyzed and are descriptive. The results showed the kind of MP-ASI ASI MP is given a homemade (local) as much as 58.2% and 41.8% giving the MP-ASI purchased (the manufacturer). The age of the giving of the MP-ASI aged less than 6 months as much as 60.0% and 40.0% (? 6 months). The frequency of the giving of the MP-ASI less appropriate i.e. 56.4% and 43.6% accordingly. Data nutritional status showed 92.7% good nutritional status and 7.3% have a better nutritional status. Not found status of poor nutrition and nutritional status.Keywords: The pattern of MP-ASI, the nutritional status of infants.